Business statistics for MBA with computer applications - Martin, Matt L.; Benson, P. George (Quezon City, Philippines : JMC Press Inc., 1999)
Business statistics for MBA with computer applications is a comprehensive textbooks covering the wide spectrum of statistics. It is designed to provide the users wide choice of statistical topics he need on his concerns.
Chapter 1. What is Statistics? -- Chapter 2. Graphical Description of Data -- Chapter 3. Numerical Descriptive Measures -- Chapter 4. Probability -- Chapter 5. Discrete Random Variable -- Chapter 6. Continuous Random Variable -- Chapter 7. Sampling Distribution -- Chapter 8. Estimation and A Test of Hypothesis: Single Sample -- Chapter 9. Two Samples: Estimation and Test of Hypothesis -- Chapter 10. Simple Linear Regression -- Chapter 11. Multiple Regression -- Chapter 12. Introduction to Model Building -- Chapter 13. Time Series: Index Numbers and Descriptive Analyses -- Chapter 14. Time Series: Models and Forecasting -- Chapter 15. Analyses of Variance -- Chapter 16. Nonparametric Statistics -- Chapter 17. The Chi-Square Test and The Analysis of Contingency Tables -- Chapter 18. Decision Analysis Using Prior Information -- Chapter 19. Decision Analysis Using Prior and Sample Information -- Chapter 20. Surveying Sampling.
Includes index.
Keywords: BUSINESS